Value Chain Analysis and Marketing Performance of Vegetable Subsector: A Case of Sindupalchowk District, Nepal - Sharma, Manoj (International Journal of Applied Sciences and Biotechnology, 2019)
This study assessed value chain and marketing performance of vegetable subsector of Sindupalchowk district, Nepal with the objectives of identifying the value chain actors and their roles, analyzing the market channel and identifying the problems related to production and marketing system The study was based on both primary and secondary data. The primary data were collected from 84 households that were selected purposive proportionately. The study showed major vegetable value chain actors as input suppliers, producers, bulk traders, retailers, wholesalers and consumers. The total amount of vegetable production was 29.73 tons with productivity of 7.2 tons/ha transacting 17.92 tons of vegetables through four marketing channels. The channel transacting the vegetables to consumers directly by producers was found to be dominant in terms of volume of vegetable which represented 71.75% of total vegetable supplied by farmers (12.86 tons). The bulk traders supplied 18.97 % of vegetables to Kathmandu and 8.77% to consumers of Sindupalchowk district through retailers. The wholesalers were of least volume transacting actor to consumers through retailers (0.51%). The study suggests that Government of Nepal should focus on development of marketing infrastructures to provide equitable market sharing to actors. Int. J. Appl. Sci. Biotechnol. Vol 7(4): 453-458